Greenwashing in the food industry: A systematic review exploring the current situation and possible countermeasures - Widya Satya Nugraha; Dávid Szakos; Miklós Süth; Gyula Kasza (Cleaner and Responsible Consumption, 2024)
This research presents a clear overview of greenwashing practices in the food industry, along with instances in the academic literature. In this work, a bibliometric analysis covering over 711 articles from the Scopus database was carried out. According to the findings, research on greenwashing in general has expanded dramatically in the previous ten years, indicating an increasing importance for the upcoming years. While greenwashing is an established phenomenon in the food industry and an emerging topic among consumers, relatively few research papers are available on the subject; this review identified 16 papers that met the inclusion criteria. The review offers a detailed analysis of these papers. Key factors contributing to greenwashing practices in the food industry include advertising, access to information, transparency, knowledge, trust, and labelling. The review also identifies six major subtopics that significantly influence the food industry: retailers, corporate social responsibility, consumer research, food supply chain, and stakeholders. This study aims to serve as a valuable reference for policymakers and scholars who are determining the future path of greenwashing research. This review also aligns with the focus of the research agenda of several nations, and the EU, to act firmly against greenwashing practices and deceptive environmental claims.